2013
DOI: 10.1002/stc.1586
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion monitoring of post-tensioned concrete structures using fractal analysis of guided ultrasonic waves

Abstract: This work presents a new approach based on fractal analysis of guided ultrasonic waves (GUWs) for monitoring the corrosion evolutionary path in post-tensioned systems. Fractal analysis is a new scientific paradigm that has been used successfully in many fields including biological and physical sciences. However, its application in the SHM community has been modest. The proposed approach utilizes piezoelectric transducers, permanently attached to the steel tendon, to transmit and receive GUWs. The corrosion mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 24 publications
0
27
0
Order By: Relevance
“…The AE technique is a passive method and is employed for continuous health monitoring of cables, but it cannot capture existing failure. For the damage detection in anchorage zone, GUWs technique is proved to be a very effective method and thus it has gained more and more interest [4].…”
Section: Introductionmentioning
confidence: 99%
“…The AE technique is a passive method and is employed for continuous health monitoring of cables, but it cannot capture existing failure. For the damage detection in anchorage zone, GUWs technique is proved to be a very effective method and thus it has gained more and more interest [4].…”
Section: Introductionmentioning
confidence: 99%
“…Iturrioz et al got a quantitative evaluation of damage in concrete through the fractal dimension of AE signals distribution in the damaged domain [12]. Moustafa et al presented a new approach based on fractal analysis of guided AE waves for monitoring the corrosion evolutionary path in posttensioned systems [13]. Invernizzi et al confirmed that the energy dissipation during micro crack propagation in concrete occurs in a fractal domain [14].…”
Section: Introductionmentioning
confidence: 99%
“…Moustafa et al . monitored the propagation pattern of corrosion of post‐tensioned structures by means of the fractal dimension of ultrasonic waves measured in steel tendons. Li et al .…”
Section: Introductionmentioning
confidence: 99%
“…Adhikari et al [4] proposed an integral model based on digital image processing for numerical quantification of cracks, pattern variations, and neurological connection between cracks. Moustafa et al [5] monitored the propagation pattern of corrosion of post-tensioned structures by means of the fractal dimension of ultrasonic waves measured in steel tendons. Li et al [6] identified seismic damage of shear-type building structures based on the joint implementation of time-frequency analysis and fractal dimension characteristics.…”
Section: Introductionmentioning
confidence: 99%